A short‐term in vivo model for Merkel Cell Carcinoma. Issue 6 (26th March 2018) - Bhat, Vishwanath Kumble; Krump, Corinna; Bernhart, Eva; Becker, Jürgen C.; Sattler, Wolfgang; Ghaffari‐Tabrizi‐Wizsy, Nassim
Abstract: In vivo tumor models are essential for studying the biology of cancer, identifying tumor targets and evaluating antitumor drugs. Considering the request for the minimisation of animal experiments and following the "3R"‐rule ("replacement, " "refinement, " "reduction"), it has become crucial to develop alternative experimental models in cancer biology. Several studies have already described the avian chorioallantoic membrane (CAM) model as an alternative to rodents, suitable to investigate growth, progression and metastasis of various types of cancer. In the present work, we grafted three Merkel cell carcinoma (MCC) cell lines onto the avian CAM and monitored tumor growth and development of solid tumor nodules. Morphology of xenograft was characterised histologically and immunohistochemically. Our results demonstrate CAM assay as a useful tool to study MCC pathophysiology.